THE ROLE OF MULTI ACTORS IN EMPOWERMENT OF COFFEE FARMERS BASED ON PENTA HELIX - Saputra, Yoga Aldi; Chazienul Ulum, Mochamad (Jurnal Governansi, 2022)
Community empowerment for coffee farmers in Muncar Village is carried out in collaboration with actors through the penta helix synergy model. The existence of empowerment programs for coffee farmers has gradually provided improvements in the cultivation process, post harvest process, and the marketing process. The objectives of this study was knowing, describing, and analyzing the role of each actor in the penta helix synergy model on the empowerment programs for coffee farmers in Muncar Village in terms of the process of cultivation, post harvest, and marketing. This study uses a qualitative method with a descriptive approach. The results of this study indicated that the existence of empowerment as a whole has been able to provide changes in farmer activities, starting from the process of cultivation, post harvest, and marketing towards a better order. Actors in the penta helix model collaborated together to create prosperous coffee farmers, including: First, the government through the Muncar Village Government, the Temanggung Regency Government, Dinperindagkop and Dintanpangan of Temanggung Regency. Second, the private sector through PT. Astra International Tbk. Third, academics through Sebelas Maret University (UNS). Fourth, the community through Karya Mulia's Joint Business Group and farmer groups, and the fifth is the media through Temanggung Radio. Key words: Community Empowerment, Penta Helix, Coffee Farmers, Muncar Village.